UNDERWATER OBSERVATIONS ON THE SETTLEMENT OF SPAT OF PEARL OYSTER ON THE PAARS OFF TUTICORIN - Mahadevan, S; Nayar, K Nagappan (Indian Journal of Fisheries, 2011)
The irregularly cyclic character of the pearl fishery of the Gulf ofMannar, which was long apparent, has once again been witnessed from 1961from which time there had been no fishing for oysters. It was pointed out thatin order to establish a permanent pearling industry in India cultivation ofoysters in farms as done in countries like Japan and Australia should be resortedto, so that cultured-pearl production can be attempted. Alagarswami and Qasim(1973) succeeded in their attempts to produce, on an experimental scale, culturedpearls in India. For commercial-scale production of pearls, an unfailingsupply of oysters for farming operations and nuclei implantation has to be established.